(untitled) (Revista Contexto & Educação, 2024)
Formative assessment consists of an essential process for learning, as it is configured by regulating the teaching process, based on information collected regarding students’ knowledge. Considering the influence of teachers’ conceptions on their pedagogical practice, the present work aims to characterize the reports of forty-nine teachers regarding the purpose of assessment in the school context through Content Analysis. It is observed that thirty-two teachers made reference to the elements of formative assessment in their explanation, with the majority, represented by sixteen, being at the basic level of understanding, presenting in their records references to assessment as part of the process of teaching and learning, a specific stage of formative assessment, self-assessment, recognition of difficulties in the assessment process and learning objectives. In the records of the other teachers there was no reference to any elements of the formative assessment. It is concluded that, for an evaluation practice that is more coherent with the educational objectives aimed at the global training of individuals, the concepts, purposes, instruments and subjects of formative evaluation must be explored in an intentional and systematic way in the initial and continuing training of teachers.